1993
DOI: 10.3109/01421599309006713
|View full text |Cite
|
Sign up to set email alerts
|

Using role-plays to teach palliative medicine

Abstract: Teaching of communication skills in Palliative Medicine can be achieved using a three hour exercise involving role-plays, a time of feedback and discussion, a teaching video and a reading list. Using this teaching method self-ratings of perceived skills recorded on a questionnaire before and four weeks after the exercises showed a significant increase in both undergraduates and postgraduates. The validity of these self-ratings as a tool to measure communication skills was assessed by correlating the self-ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…A questionnaire which had previously been used to ascertain the perceived skills of medical undergraduates in New Zealand 18,19 was modi®ed for GP registrars. The questionnaire (Appendix) was given to all 210 GP registrars in the West Midlands on set calendar dates over a 2-year period (1996±98) at two intervals during their 12 months as a GP registrar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A questionnaire which had previously been used to ascertain the perceived skills of medical undergraduates in New Zealand 18,19 was modi®ed for GP registrars. The questionnaire (Appendix) was given to all 210 GP registrars in the West Midlands on set calendar dates over a 2-year period (1996±98) at two intervals during their 12 months as a GP registrar.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, each respondent was asked how long they had been a GP registrar, their age, gender and the number of 6-month senior house of®cer (SHO) posts that they had undertaken. Registrars were also asked to rate from 0 to 5 on a previously validated Likert scale 18,19 whether or not their medical school teaching and then their postgraduate training had adequately prepared them to care for dying people. Statistical analysis involved both t tests for comparison of means between the different intervals during training and multiple regression analysis of the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…The breadth of interventions designed to develop communication competency outcomes were as diverse as the 47 studies reviewed. They ranged from one time classroom interventions (Anderson, 1982) to workshops lasting two or three days (Bird et al, 1993;Charlton, 1993;Dixon et al, 2001;Fallowfield et al, 1998) to more long-term continuing education programs with follow-up sessions (Booth et al, 1996;Craytor et al, 1978;Fallowfield et al, 2001;Razavi et al, 2000;Wilkinson et al, 1998). More formal processes may involve including communications skills as a component of the health professions curricula (Baile et al, 1997).…”
Section: Outcomes Of the Training Programsmentioning
confidence: 99%
“…Outcomes of training intervention Anderson, 1982 Problem to communicate with terminally ill patients Work on own solutions, discuss and hear others' views Andrews, 1998 Short course of simulated patients interviews Learning influenced by constructs and values of teacher/institution Berman and Villarreal, 1983 1 day seminar; emotional strains caring for the dying Need seminars on effective interpersonal communication skills Charlton, 1993 3 h of role-play using clinical situations Illustrated need to practice and receive feedback Faulkner, 1992 Training so patients can disclose concerns, feelings Rating impractical for trainers; interactive teaching needed Ferrell et al, 1998a,b HOPE program 9 h-5 modules on terminal illness Increased comfort communicating; culturally sensitive end of life care Hainsworth, 1996 Three classes on death and dying communications…”
Section: Studymentioning
confidence: 99%
“…In 1993, Charlton18 described using role play simulation to teach medicine communication skills to undergraduate and postgraduate medical trainees, with both groups describing an improvement in their perceived skills. Findlay et al 19 made simulated patients a key component of their communication skills teaching on a diploma in palliative medicine and demonstrated their value in teaching and assessing students but found that patients and examiners produce differing scores of a candidate's ability.…”
Section: Introductionmentioning
confidence: 99%